Selection Strategy of Drought Tolerance of Red Rice Mutant Lines - Eries D. Mustikarini; Noer Rahmi Ardiarini; Nur Basuki; Kuswanto Kuswanto (AGRIVITA, Journal of Agricultural Science, 2017)
Most of Indonesian red rice is not grown in dry land. New varieties could be breeded through mutation breeding. This research objective was to evaluate the selection strategy of drought tolerant on red rice. The study was conducted on ultisol soil in Bangka Belitung Province, Indonesia, in February 2012-February 2015. It consisted of three activities, selection M5, evaluation of selected M5 and evaluation of drought critical period on selected M6. Mutant of M5 was selected and evaluated with polyethylene glycol (PEG) -0.5 MPa and less of soil moisture. Selected M6 was evaluated to observe a critical period of drought stress. Evaluation with PEG produces five superior mutants that more vigor than the elders. Selection on low humidity shows that M5-GR150-1-9 produces higher filled grain and weight filled grain than other mutants and elders. The selected red rice line M5-GR150-1-9-13, has a better tolerance towards drought than its control. It could be obtained such mutant lines which have a high yield, early maturing and drought tolerant from the result of six generations gamma irradiation mutant selection.